Mental Health and Development in a Shack Settlement: The Case of Bhambayi - Petersen, Inge; Ramsay, Sheila (PINS-Psychology in Society, 2026)
In South African shack settlements, poverty, overcrowding, unemployment and a sense of hopelessness characterise the conditions under which people live. A growing body of knowledge reveal that mental health suffers under these conditions (Lewis and Lewis, 1979; Chambers, 1983; Levenstein, 1989) and is exacerbated by the oppressive political situation and resultant violence which characterises South Africa (Vogelman, 1986; Foster et al, 1987; Butchart and Seedat, 1990). The purpose of this paper is to evaluate the work of the Community Mental Health Project (CMHP) in a South African shack settlement and to draw out lessons that can inform future mental health programmes in similar contexts. In order to understand the context in which the project has been operating, we begin with a brief description of Bhambayi, the shack settlement in which the project has been located. We then go on to examining the goals and conceptual framework of the CMHP, as well as its structure and its activities. Lessons are then drawn which inform the relationship between mental health and development and increase our understanding of the position of mental health services in deprived communities, particularly shack settlements.